Recanalization, reperfusion, and recirculation in stroke. Issue 12 (December 2017) - Zhang, John H; Obenaus, Andre; Liebeskind, David S; Tang, Jiping; Hartman, Richard; Pearce, William J
Recirculation, from arterial inflow routes through venous outflow pathways, was conceptualized in stroke research 50 years ago. As new technologies were developed, blocked arteries could be reopened, capillaries could be reperfused, and the use of recanalization and reperfusion grew to dominate therapeutic strategies. These approaches overwhelmingly focused on restoration of arterial and capillary inflow, but not on veins even though venous disorders may initiate or exacerbate brain injury. In this commentary, we advance the term "recirculation" after "recanalization" and "reperfusion" as a primary concept of stroke pathophysiology that targets the restoration of both the arterial and venous cerebral circulations.